Investigating Human Influence on Offshore Terrestrial Organic Carbon Trends in a High-Energy Delta: The Ayeyarwady Delta, Myanmar - Evan R. Flynn; Steven A. Kuehl (Journal of Marine Science and Engineering)
The continental margin is a major repository for organic carbon; however, anthropogenic alterations to global sediment and particulate terrestrial organic carbon (TerrOC) fluxes have reduced delivery by rivers and offshore burial in recent decades. Despite the absence of mainstem damming, land use change in the Ayeyarwady and Thanlwin River catchments in Myanmar has accelerated over the last 50 years. As a result, deforestation and landscape erosion have likely altered fluvial fluxes to the Northern Andaman Sea shelf; however, the magnitude and preservation of geochemical signals associated with development are unknown. Utilizing elemental and bulk stable and radioisotope analysis, this study investigates spatial and temporal trends in sediment sources and TerrOC concentrations to identify the potential impacts of recent (<100 years) offshore development. While our results demonstrate an along-shelf trend in provenance and TerrOC concentrations, temporal (downcore) trends are not observed. We attribute this observation to frequent, large-scale seabed resuspension and suggest that extensive mixing on the inner shelf creates a low-pass filter that effectively attenuates such signatures. This is in contrast to other large Asian deltas, where signals of human landscape disturbance are clearly preserved offshore. We predict that planned mainstem damming in Myanmar will result in larger alterations in sediment and TerrOC supply that may become apparent offshore in the near future.